The unfinished democratization of Europe - Eriksen, Erik Oddvar, 1955- (Oxford : Oxford University Press, 2009)
The widening & deepening of the European Union have brought to the fore the question of democracy at the European level. This book contributes to democratic theory under conditions of globalization & complex interdependence as well as to the understanding of the EU from a democratic point of view.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; Democratization -- European Union countries; European Union countries -- Politics and government